Heterogeneous traders, price-volume signals, and complex asset price dynamics - Frank H. Westerhoff (Discrete Dynamics in Nature and Society)
We seek to develop a novel asset pricing model with heterogeneous traders. Fundamental traders expect that asset prices converge towards their intrinsic values, whereas chart traders rely on both price and volume signals to determine their orders. To be precise, the larger the trading volume, the more they believe in the persistence of the current price trend. Simulations of our nonlinear deterministic model reveal that interactions between fundamentalists and chartists may cause intricate endogenous price fluctuations. Contrary to the intuition, we find that chart trading may increase market stability.